KEWIRAUSAHAWANAN DAN KARAKTERISTIK INDIVIDU WIRAUSAHA RAMBAK DI DESA BANGSAL MOJOKERTO - Sirot Irjianto (Manajemen Bisnis, 2011)
PT. MPM Motor Cabang Ngawi Jawa TimurEmail: cutex_moxer@yahoo.co.idABSTRACTThe research is a survey descriptive research at rambak home-business in Bangsal Village MojokertoRegency. The first research purpose is finding out entrepreneurship spirit consisted of self confidence,task and result orientation, risk taking, leadership, originality, and orientation for future. Second, tofind out individual characteristics consisted of sex, age, business time length, education, and income.Third, is to find out entrepreneurship spirit from individual characteristic in detail. Analytical tools usedare scale rank analysis and cross tabulation. The result of research show that the entrepreneurshipspirit consist of self confidence, task and result orientation, risk taking, leadership, originality, andorientation for future are carried out in home business. Then, the individual characteristics consist ofsex, age, business time length, education, and income.Keywords: entrepreneurship spirit, individual characteristic, home- business